Can anthropometric measures discriminate biochemical factors in physically active women over the age of 50 years? - Petreca D.R.* (2016)
© J. Phys. Educ., 2016.In Brazil, higher rates of overweight and obesity are observed in the age group of 55-64 years. These body composition disorders may be associated with metabolic changes and it is therefore important to investigate which anthropometric measures can discriminate levels of biochemical changes. The aim of this study was to analyze by means of sensitivity and specificity if anthropometric variables can discriminate biochemical changes in cholesterol, triglycerides and glucose in physically active women over the age of 50 years. A total of 139 women aged 50 years and older who take part in regular physical activity participated in the study. The following anthropometric variables were analyzed: body mass index (BMI), waist circumference (WC), waist-to-hip ratio (WHR), waist-to-height ratio (WHtR), conicity index, and body fat percentage (BF%). The biochemical variables analyzed were blood glucose, triglycerides, and total cholesterol (TC). Descriptive statistics and ROC curves were used. The results showed that BMI, WC, WHR, WHtR and BF% were able to discriminate increased blood glucose. The WHR discriminated elevated triglycerides, while none of the anthropometric variable was able to discriminate increased TC. In conclusion, some anthropometric variables can be used to identify an increased risk of biochemical changes, such as elevated blood glucose and triglycerides, in physically active women over the age of 50 years.